Study on psychological effect from colour in interior spaces among architecture students of UiTM Seri Iskandar / Arif Luqman Nazeri ... [et al.] - Nazeri, Arif Luqman; Yusof, Ahmad Faisol; Abdul Aziz, Azhan; Sayed Abul Khair, Sayed Muhammad Aiman (2023)
Colour is a part of the main role in interior spaces to give impact to human psychology, performance, and behavior. Colour can also enhance the interior spaces’ function and improve the environment in the space. Choosing colour with the concept in mind can also help to create a more aesthetic space and one that is loved by the client. This paper provides a brief conceptual overview of the significance of colour in interior space and how human psychology reacts to it. A study on previous research and references such as books will be done to help providing a fact on the importance aspect of using up colour in interior spaces and its effects to human psychology. Questionnaire will be sort out to the architecture students in UiTM Perak Branch, Seri Iskandar Campus to interpret how the colour psychology give benefits to designing interior spaces. It is hoped that this paper may possibly provide guideline on psychological effect from colour in interior spaces.